728 Children, young people and parent reported qualitative findings of a national service evaluation for the structured education module for children with type 1 diabetes: SEREN 'diabetes at diagnosis'. (17th August 2022) - D'Souza, Rashmi; Hawkes, Esther; Ryan, Matthew; Baker, Claire; Davies, Yvonne; R-Screen, Judith; Price, Jonathan; Pryce, Rebekah; D'Souza, Nirupa
Abstract : Aims: To evaluate the user-reported usefulness and effectiveness of the first structured education module for children with Type 1 Diabetes Mellitus (T1DM) in Wales – SEREN 'Diabetes at Diagnosis'. Methods: This reports the qualitative findings from a national retrospective questionnaire-based service evaluation. The SEREN programme is the first standardised Diabetes structured education programme for children and young people (CYP) and their families in Wales. The first module, 'Diabetes at Diagnosis', delivers education to empower CYP and their families with self-management of T1DM after diagnosis. It was introduced across Wales in 2016-17. 12/14 paediatric diabetes centres in Wales took part in the evaluation. A national diabetes register was used to select the pre-SEREN cohort of children diagnosed with T1DM one year before the introduction of the module and the post-SEREN cohort were diagnosed one year after its introduction. Primary outcomes were CYP and parent reported user-friendliness and effectiveness. Data from free text questionnaire responses were subjected to a thematic analysis. The evaluation also included clinical outcomes (Quality of life using PedsQL scoring, HbA1c at six and 12 months, service engagement and diabetes-related hospital admissions in the first year) which have been reported separately. 1 Results: 89/106 responded pre-SEREN and 108/115 post-SEREN, with no demographic differences in age, sex, ethnicity, deprivation quintile and HbA1c at diagnosis. Of these, 45 CYP and their families pre-SEREN, and 93 post-SEREN provided free text feedback on what they felt was useful in the education they received and what could be improved. SEREN resources were frequently described as 'practical', 'easy to understand' and 'helped with self-management'. Suggestions for improvement included provision of more emotional and psychological support, further sessions, information on long term impact and help to engage with other families already living with T1DM. Quantitative results from the service evaluation are published elsewhere. 1 Conclusion: This reports qualitative findings of a national service evaluation of the only standardised T1DM structured education programme in use for CYP and their families throughout Wales. These findings have helped inform and improve the revision of the first module, 'Diabetes at Diagnosis'. Further evaluation from the cohort who have now received subsequent SEREN modules and health care professionals that deliver the programme is required to evaluate the full impact of the SEREN programme. With the rising incidence of T1DM, it is important that health systems invest in improving health responsiveness and patient empowerment for CYP and families living with this life-long condition. Reference: D'Souza RS, Ryan M, Hawkes E, et al. Questionnaire-based service evaluation of the efficacy and usefulness of SEREN: a structured education programme for children and young people diagnosed with type 1 diabetes mellitus. BMJ Open Quality 2021;10:e001337. doi:10.1136/bmjoq-2021-001337